CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

If a, b, c, d, e, f are in AP, then (d -b) is equal to


  1. 2 (a - b)                

  2.  e - c 

  3. 2 x (c - b)


Solution

The correct options are
B

 e - c 


D

2 x (c - b)


If a, b,c,d,ef are in A.P, then the common difference, c.d is equal to (b -a).

We can write the A.P as

a+c.da+2(c.d)a+3(c.d)a+4(c.d)a+5(c.d)abcdef

d - b = 2 c.d

We will go through the options and find if it is correct

(A)2(a-b) =-2 c.d                    (B)e - c=2 c.d

(c)fc2=32c.d   (D)2(c -b) =2 c.d

flag
 Suggest corrections
thumbs-up
 
0 Upvotes



footer-image